Compositional and lithological variation of the Platreef on the farm Nonnenwerth, northern lobe of the Bushveld complex : implications for the origin of Platinum-group elements (PGE) mineralization - Maier, Wolfgang D. (University of Pretoria, 2013)
Thesis (PhD)--University of Pretoria, 2009.